POLYGENIC RISK BURDEN AND THE NARROWING OF THE SAFE OPERATIVE WINDOW IN ACUTE CALCULOUS CHOLECYSTITIS (International Congress on Economics, Management and Business Studies, 2026)
Emergency cholecystectomy for acute calculous cholecystitis carries a disproportionate share of preventable morbidity in abdominal surgery. Published conversion rates from laparoscopic to open cholecystectomy range from 8% to 22% [1], and are largely determined by whether surgery is performed before or after dense perivesical infiltration has consolidated the tissues of Calot's triangle. Tokyo Guidelines 2018 classify severity at presentation but offer no instrument for predicting how rapidly a given patient's disease will progress to the gangrenous or perforative stage [2]. In clinical practice, this gap is bridged by sequential reassessment, a strategy that works well for the majority but fails for the subset of patients who deteriorate within the first 12 hours of admission.